2019
DOI: 10.3389/fonc.2018.00679
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Inhibits Natural Killer/T-Cell Lymphoma by Modulation of VEGF Expression and Mitochondrial Function

Abstract: Extranodal nasal-type natural killer/T-cell lymphoma (NKTCL) is an Epstein-Barr virus (EBV)-associated lymphoma with a strong tendency relapse or be refractory in response to chemotherapy. Development of a new strategy for NKTCL treatment is still quite necessary. In this study, we found that aspirin treatment suppresses VEGF expression in NKTCL SNK-6 cells. Further investigation showed that aspirin treatment increases histone methylation in the range of −100~0 that is proximal to the transcription start site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…Tf-D-HKC8 peptide dissociates HKDC1 from VDAC1 and induces significant ROS overgeneration, subsequently resulting in EBV DNA damage and P-gp suppression. This is consistent with our previous finding that ROS overgeneration suppresses EBV-positive ENKTL cells [ 7 ]. P-gp is a membrane transporter coded by multiple drug resistance 1 gene that excretes drugs from the cytoplasm, resulting in high resistance to chemotherapy [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Tf-D-HKC8 peptide dissociates HKDC1 from VDAC1 and induces significant ROS overgeneration, subsequently resulting in EBV DNA damage and P-gp suppression. This is consistent with our previous finding that ROS overgeneration suppresses EBV-positive ENKTL cells [ 7 ]. P-gp is a membrane transporter coded by multiple drug resistance 1 gene that excretes drugs from the cytoplasm, resulting in high resistance to chemotherapy [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…HKDC1 could be a novel potential therapeutic target for antitumor drug development [ 20 22 , 33 ]. ENKTL is highly resistant to current multidrug chemotherapies with a poor prognosis [ 6 , 7 ]. Many potential risk factors for ENKTL have been described [ 34 ], and EBV infection is considered to be the strongest one [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASA inhibits cyclooxygenase-1 (COX-1) in platelets, thereby blocking the production of prostaglandins [ 48 ] and the production of thromboxan-A 2 (TXA 2 ), leading to reduced platelet activation and aggregation [ 49 ]. Previous studies have demonstrated that ASA and its derivatives can alter the VEGF expression, leading to suppressed angiogenesis as a consequence, although how ASA decreases the VEGF expression remains unknown [ 50 , 51 , 52 , 53 ]. For example, in hypertensive patients who had significantly higher plasma levels of VEGF, there were significant reductions in VEGF plasma concentrations while following the treatment with ASA for three months, indicating that the use of ASA leads to a reduction in intraplatelet angiogenic growth factors and platelet activation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin and salicylate have been shown to evoke mitochondrial dysfunction. These two drugs induced loss of mitochondrial membrane potential (ΔΨ m ), decreased ATP production, and increased ROS generation in different cell types [ 23 , 24 , 25 ]. However, little is known about their effects on depolarization and role in mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%